Is public investment in construction and in R&D, growth enhancing? A PVAR Approach - Afonso, António (2022)
We study the impacts of public investment, notably in construction and in R&D on economic growth and of crowding-out effects on private investment. For this purpose, we use Panel Vector Autoregression (PVAR) models and the Generalised Method of Moments (GMM) approach for 40 advanced and emerging countries from 1995 to 2019. Our findings are as follows: i) innovations in public investment have more positive effects on GDP growth and private investment in emerging economies; ii) the positive impulse of public investment on private sector is pronounced and significant in emerging economies; iii) government construction investment has a more positive effect on economic growth in emerging economies; iv) innovations in public construction crowd-out private investment spending in advanced countries; v) emerging economies benefit from public R&D investment; vi) the public investment multiplier of the full sample is 1.67, while it is 0.87 for advanced economies and 2.29 for emerging economies.